Biosynthesis and Emission of Stress-Induced Volatile Terpenes in Roots and Leaves of Switchgrass (Panicum virgatum L.) - Muchlinski, Andrew; Chen, Xinlu; Lovell, John T.; Köllner, Tobias G.; Pelot, Kyle A.; Zerbe, Philipp; Ruggiero, Meredith; Callaway, LeMar; Laliberte, Suzanne; Chen, Feng; Tholl, Dorothea (Frontiers in Plant Science, 2019)
Switchgrass (Panicum virgatum L.), a perennial C4 grass, represents an important species in natural and anthropogenic grasslands of North America. Its resilience to abiotic and biotic stress has made switchgrass a preferred bioenergy crop. However, little is known about the mechanisms of resistance of switchgrass against pathogens and herbivores. Volatile compounds such as terpenes have important activities in plant direct and indirect defense. Here we show that switchgrass leaves emit blends of monoterpenes and sesquiterpenes upon feeding by the generalist insect herbivore Spodoptera frugiperda (fall armyworm) and in a systemic response to the treatment of roots with defense hormones. Belowground application of methyl jasmonate also induced the release of volatile terpenes from roots. To correlate the emission of terpenes with the expression and activity of their corresponding biosynthetic genes, we identified a gene family of 44 monoterpene and sesquiterpene synthases (mono- and sesqui-TPSs) of the type-a, b, g, and e subfamilies, of which 32 TPSs were found to be functionally active in vitro. The TPS genes are distributed over the K and N sub-genomes with clusters occurring on several chromosomes. Synteny analysis revealed syntenic networks for approximately 30-40% of the switchgrass TPS genes in the genomes of Panicum hallii, Setaria viridis, and Sorghum bicolor suggesting shared TPS ancestry in the common progenitor of these grass lineages. Eighteen switchgrass TPS genes were substantially induced upon insect and hormone treatment and the enzymatic products of nine of these genes correlated with compounds of the induced volatile blends. In accordance with the emission of volatiles, TPS gene expression was induced systemically in response to belowground treatment, whereas this response was not observed upon aboveground feeding of S. frugiperda. Our results demonstrate complex above and belowground responses of induced volatile terpene metabolism in switchgrass and provide a framework for more detailed investigations of the function of terpenes in stress resistance in this monocot crop.